Sixteen prescribed Chinese herbal medicines provide time-dependent cardiorenal and survival benefits in patients with overall and advanced diabetic kidney disease: a real-world study in Taiwan - Chen, Hsiao-Tien; Tung, Chien-Hsueh; Yu, Ben-Hui; Chen, Yi-Chun (Frontiers in Pharmacology, 2024)
Background: A causal connection between oxidative stress and inflammation in diabetes, along with its associated renal and cardiovascular complications, has been established. Sixteen prescribed potentially renoprotective Chinese herbal medicines for diabetic kidney disease (PRCHMDKD), which are scientific Chinese medicine (botanical drug) and categorized into five classes (clearing heat, nourishing yin, dampness dispelling, tonifying qi, and harmonizing formulas), exhibit shared antioxidative properties and target multiple oxidative stress pathways. However, the time-response, cumulative effects, and safety (hyperkalemia risk) of these sixteen PRCHMDKD on cardiorenal and survival outcomes in patients with overall and advanced DKD remain unresolved. Methods: This retrospective cohort study analyzed national health insurance claims data in 2000-2017. Four statistical methods, including Cox proportional hazards models, complementary restricted mean survival time (RMST), propensity score matching, and competing risk analysis for end-stage renal disease (ESRD), were employed to investigate this relationship. The study included 43,480 PRCHMDKD users and an equal number of matched nonusers within the overall DKD patient population. For advanced DKD patients, the cohort comprised 1,422 PRCHMDKD users and an equivalent number of matched nonusers.Results: PRCHMDKD use in overall and advanced, respectively, DKD patients was associated with time-dependent reductions in adjusted hazard ratios for ESRD (0.66; 95% CI, 0.61-0.70 vs. 0.81; 0.65-0.99), all-cause mortality (0.48; 0.47-0.49 vs. 0.59; 0.50-0.70), and cardiovascular mortality (0.50; 0.48-0.53 vs. 0.61; 0.45-0.82).Significant differences in RMST were observed in overall and advanced, respectively, DKD patients, favoring PRCHMDKD use: 0.31 years (95% CI, 0.24-0.38) vs. 0.61 years (0.13-1.10) for ESRD, 2.71 years (2.60-2.82) vs. 1.50 years (1.03-1.98) for allcause mortality, and 1.18 years (1.09-1.28) vs. 0.59 years (0.22-0.95) for cardiovascular mortality. Additionally, hyperkalemia risk did not increase. These findings remained consistent despite multiple sensitivity analyses. Notably, the cumulative effects of utilizing at least four or five classes and multiple botanical drugs from the sixteen PRCHMDKD provided enhanced renoprotection for patients with both overall and advanced DKD. This suggests that there is involvement of multiple targets within the oxidative stress pathways associated with DKD.This real-world study suggests that using these sixteen PRCHMDKD provides time-dependent cardiorenal and survival benefits while ensuring safety for DKD patients.